Transparansi dan Keadilan dalam Pengelolaan Ghanimah oleh Nabi Muhammad SAW sebagai Cerminan Akuntabilitas Keuangan Islam - Uswatun Hasanah (JURNAL SYIAR-SYIAR, 2024)
This study aims to explore the principles of transparency and justice in the management of ghanimah (war booty) by Prophet Muhammad SAW as a reflection of Islamic financial accountability and their relevance to modern financial management. Using a literature review method, this research collects and analyzes primary sources such as the Qur'an and Hadith, along with secondary sources including Islamic historical literature, academic journals, and contemporary books on Islamic finance. The findings reveal that transparency and justice in ghanimah management were implemented through public participation, clear guidelines, equitable distribution, and strict accountability to both Allah and society. These principles form the foundation of Islamic financial accountability and are highly relevant in modern financial contexts. For example, Islamic financial institutions adopt transparency, ethical governance, and fairness to enhance public trust and ensure sustainable resource management. The research concludes that the ghanimah management model exemplifies ethical and accountable financial practices, offering valuable lessons for modern financial systems in creating more just and inclusive frameworks